Mobile connectivity: A vector for rural transformations in the WAEMU? - Joël Cariolle (Fondation pour les études et recherches sur le développement international (FERDI), 2024)
Digitalisation presents a significant challenge for the development of rural areas in sub-Saharan Africa, where basic infrastructure and public services are often lacking, the financial sector is dysfunctional, insecurity is widespread, climatic conditions are often unfavourable, and farmers are geographically distant from agricultural markets (Aker & Mbiti, 2010; De Janvry & Sadoulet, 2022; Suri & Udry, 2022; Aker & Cariolle, 2023). These obstacles to development are particularly pronounced in rural communities of West African countries, which rely heavily on rain-fed agriculture and are increasingly vulnerable to climatic, geopolitical, and socio-political risks. These risks have negative repercussions on food security, agricultural commodity prices, and productivity (De Longueville, 2020; Sers & Mughal, 2020; Bouet et al., 2023; McGuirk & Nunn, 2023, 2024).
Keywords: 330; West African Economic and Monetary Union (WAEMU); Digital development; Mobile phones